INVERSI MODEL BASED UNTUK GAMBARAN LITOLOGI BAWAH PERMUKAAN - FR, Tabah; Danusaputro, Hernowo (JURNAL SAINS DAN MATEMATIKA, 2010)
ABSTRACT-IncreosW of occuracy underground level imaging can be performed by using seismic inversion method. Apply inversion method to seismic data produce acoustic impedance value. Acoustic impedmce related directly with rock characteristic, so can be separating lithology. Based model irwersion built geologt model, then conelated with seismic data, upgrading iterative to get good suitable with seismic data. Result of based model funersioncan be able to produce result of inversion which is having same trend acoustic impedance with the original data seismic, thot also between syltthetic seismic and original seismic, so can be separating lithologt boundary conectly os vertical or continue as lateral.Key word: acoustic impedance, based model inversion, lithologyPermalink : http://ejournal.undip.ac.id/index.php/sm/article/view/2950